Knockout of elF4E using CRISPR/Cas9 for large-scale production of resistant cucumber cultivar against WMV, ZYMV, and PRSV - Fidan, Hakan; Calis, Ozer; Ari, Esin; Atasayar, Aydin; Sarikaya, Pelin; Tek, Mumin Ibrahim; Izmirli, Ahmet; Oz, Yasemin; Firat, Gulsah (Frontiers in Plant Science, 2023)
CRISPR/Cas9 is one of the most robust technologies for plant breeding enabling precise and efficient modifications in a genome. This technology is being used for the manipulation of target genes in a host to develop resistance against the plant pathogens. Cucumis sativus elF4E is one of the target genes playing a key role in viral infection during interaction with potyvirus viral proteins genome-linked (VPg). Nevertheless, the allelic and positional effect of elF4E mutations in C. sativus is to be clarified in elF4E-VPg interaction. Besides, there are entanglements in the massive production of pathogen-resistant cultivars suitable for commercial production using CRISPR/Cas9 technology. Therefore, we targeted different positions of the elF4E in G27 and G247 inbred lines, using specific gRNA1 and gRNA2 for the first and third exons, respectively; and 1221 transgene-free plants were selected in segregated T1 generation, where 192 G27 and 79 G247 plants had the least mutation at Cas9 cleavage site of gRNA1 or gRNA2. Crossing was performed to see allelic effects of elfF4E mutations in F1 populations that were homozygous and heterozygous single (elF4E_1DEL or elF4E_3DEL) and double (elF4E_1-3DEL) mutants. Disease symptoms of watermelon mosaic virus (WMV), papaya ringspot virus (PRSV) and zucchini yellow mosaic virus (ZYMV) were evaluated in both non-edited and edited F1 plants, and we did not observe any symptom in homozygous elF4E_1-3DEL and elF4E_1DEL mutants. However, homozygous elF4E_3DEL was positive in RT-PCR, even if there were no significant symptoms on the inoculated leaves. ELISA and qRT-PCR indicated lower viral accumulation in homozygous elF4E_3DEL than heterozygous and non-edited plants. Regeneration and transformation protocols were also optimized comprehensively for both the genotypes. The average number of shoots/100 explants were determined for both G27 and G247 as 13.6 and 18.0, respectively. We couldn’t detect any distinguishing difference between the non-edited and edited F1 plants for yield and morphology. Our results demonstrate an effective route for mass-production of viral resistant cultivars of cucumber to WMV, ZYMV and PRSV. In this way, the pathogen-resistant cultivars could be generated to reduce the losses caused by these pathogens in cucumber production.